"No Justice, No Peace" and the Right to Self-Determination: An Interview with Gary Grant and Naeema Muhammed of the North Carolina Environmental Justice Network. (August 2014) - Slatin, Craig; Scammell, Madeleine Kangsen
This is an interview with Gary Grant and Naeema Muhammed, leaders of the North Carolina Environmental Justice Network. Each of them talks about where they grew up, their politicization, how their paths crossed, their work together after Hurricane Floyd, and the unique challenges of organizing for social justice for black communities in the South. We learn of their fight against concentrated animal feeding operations (CAFOs), primarily for the hog trade, and they take us up to North Carolina's Moral Monday protests of 2013 against legislation that threatens voting rights, public education, access to medical services, unemployment benefits, workers rights, occupational and environmental health, and women's access to reproductive health care. We are grateful to these two friends of New Solutions for their contribution to the journal, and we hope that their insights regarding struggles for social and environmental justice can serve as guides for us all.